Big Data Technology and its Importance for Decision-Making in Enterprises - Milan Kubina; Gabriel Koman (Communications - Scientific letters of the University of Zilina, 2016)
Rapid development in the field of information-communication technologies, which has been recorded in recent years, caused the increase from 40 to 50% in the volume of data in companies last year. At present enterprises are able to use only a quarter of the data available. It is expected that by 2020, the volume of data will have reached 35 zettabytes [1]. By analyzing large amounts of data, it is possible to get the information important for an enterprise which will facilitate decision-making process of managers. Technology for large volume data called Big Data is nowadays largely employed for effective use of data.